2018
DOI: 10.5232/ricyde2018.05301
|View full text |Cite
|
Sign up to set email alerts
|

Emotional regulation and physical recovery in young athletes of individual and collective sport modalities. [Regulación emocional y recuperación física de los jóvenes deportistas en modalidades deportivas individual y colectiva].

Abstract: Due to the influence of positive and negative affects experienced during competition on sports performance, emotional regulation is one of the psychological variables that are more interesting to the sport psychology field. In this sense, this study analyzes how the use of reappraisal and suppression stimulates or hampers the physical recovery of young athletes. All of this taking into account the mediating role of self-efficacy and cognitive anxiety experienced during competition. Three hundred Chilean athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(44 reference statements)
3
6
1
1
Order By: Relevance
“…Gatti et al [59] and Kosmidou et al [26], determined that feelings towards physical self-concept are negatively influenced by the drastic bodily changes that occur at these ages, pressure from the family and the trainer, competitions and excessive concern to stay thin [60,61]. This would agree with the data found in this study, since the approach of the championships intensifies the trainings and, with it, the pressure to which they are submitted, carrying consequences in the self-esteem, the physical appearance and the security in oneself in general [62].…”
Section: Discussionsupporting
confidence: 87%
“…Gatti et al [59] and Kosmidou et al [26], determined that feelings towards physical self-concept are negatively influenced by the drastic bodily changes that occur at these ages, pressure from the family and the trainer, competitions and excessive concern to stay thin [60,61]. This would agree with the data found in this study, since the approach of the championships intensifies the trainings and, with it, the pressure to which they are submitted, carrying consequences in the self-esteem, the physical appearance and the security in oneself in general [62].…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, suppression, social isolation and withdrawal were associated with low psychological well-being., At the opposite, strategies such as problem-directed action and planning, attentional deployment through distraction, seeking social support, cognitive change by reappraisal, response modulation by active physiological regulation, as well as venting and regulated expression, acceptance and gratitude/self-reward, have been found to be positively correlated with psychological wellbeing. However, as observed in previous studies, the functionality of emotional regulation strategies and their relationship with well-being varies depending on the situations and interactions that occur with others [37]. Therefore, it is essential to conduct more studies that allow us to verify the functionality of emotional regulation strategies and their relationship with well-being in different contexts.…”
Section: Wellbeing and Emotional Regulationmentioning
confidence: 85%
“…Research has shown that people who use more functional regulation strategies experience high psychological well-being [4,36]. Therefore, well-being measures are also important to verify the functionality of emotional regulation strategies in different situations [37]. Specifically, some studies have focused on studying the relationship between regulation strategies and psychological or eudaimonic well-being (which refers to the extent to which individuals perceive their lives to be meaningful, purposeful, and fulfilling), while others have also related them to measures of hedonic well-being (which refers to the subjective experience of pleasure, happiness, and life satisfaction) [38].…”
Section: Wellbeing and Emotional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta discrepancia específica, concuerda con otros estudios, donde el deporte en equipo ha evidenciado propiciar una mayor confianza en los miembros en comparación a las prácticas individuales (Molina, Oriol, & Mendoza, 2017;Cantón-Chirivella et al, 2015;Pinto & Vásquez, 2013), lo que podría suponer que al favorecer la autoconfianza, las prácticas colectivas incrementarían indirectamente el rendimiento y el estado emocional positivo de los deportistas (e.g. Feltz, 2007;Martínez-Romero, Molina, & Oriol-Granado, 2016), teniendo el potencial de disminuir la ansiedad cognitiva y somática (Cervantes, Rodas, & Capdevila, 2009;Prados, García, & Lluch, 2011).…”
Section: Discussionunclassified